To solve the compound inequality \(-2 \leq 2x + 1 - 4 < 1\), we first simplify it.
-
Combine constants in the middle part: \[ 2x + 1 - 4 = 2x - 3 \]
Thus, the compound inequality simplifies to: \[ -2 \leq 2x - 3 < 1 \]
-
Now we will split it into two parts:
- For the left part: \(-2 \leq 2x - 3\)
- For the right part: \(2x - 3 < 1\)
Solving the left part: \[ -2 \leq 2x - 3 \] Add 3 to both sides: \[ 1 \leq 2x \] Divide by 2: \[ \frac{1}{2} \leq x \quad \text{or} \quad x \geq \frac{1}{2} \]
Solving the right part: \[ 2x - 3 < 1 \] Add 3 to both sides: \[ 2x < 4 \] Divide by 2: \[ x < 2 \]
- Putting it all together, we have: \[ \frac{1}{2} \leq x < 2 \]
The solution in interval notation is \([\frac{1}{2}, 2)\) or in set notation: \[ {x : \frac{1}{2} \leq x < 2} \]
Given your options, it seems like there might be some formatting issues. The closest option to represent this solution is: \[ {x : \frac{1}{2} \leq x < 2} \]
Make sure to confirm the available options match what was presented!